Perkembangan Neo-Spiritualisme di Kalangan Remaja Kelurahan Kenangan, Lingkungan VII, Kecamatan Percut Sei Tuan - Adawiyah, Rabiatul; Harahap, Indra (UIN Sumatera Utara, 2025)
This study explores the development of neo-spiritualism among youth, particularly in Kelurahan Kenangan, Lingkungan VII, Kecamatan Percut Sei Tuan. Neo-spiritualism emerges as a new form of spirituality that is more flexible, personal, and detached from formal religious doctrines, responding to the spiritual emptiness experienced in modern life and the declining authority of traditional religious institutions. Using a qualitative-descriptive approach, the research investigates the spiritual experiences and perspectives of youth through interviews, questionnaires, and literature studies. The findings reveal that many adolescents are open to modern spiritual practices such as meditation, self-healing, journaling, and mindfulness, often discovered through social media platforms. The primary drivers behind the growth of neo-spiritualism include the desire for a more personal spiritual experience and the influential role of digital media as a space for exploring life's meaning. Despite this trend, the study identifies diverse spiritual characteristics, some youth fully detach from formal religion, while others maintain Islamic beliefs while adopting contemporary practices. This research provides insights into the shifting patterns of religiosity at the local level and highlights the importance of contextual and adaptive spiritual approaches in guiding today's younger generation